Measuring evaporation distribution of mud brick and rammed earth. Issue 1 (8th April 2014) - Fodde, Enrico; Watanabe, Kunio; Fujii, Yukiyasu
Abstract : Purpose: – Salt weathering is one of the most common agents of decay of Central Asian earthen sites and is in function of water evaporation from the wall surface. Soon after excavation the earthen walls and the stupa of the Buddhist temple of Ajina Tepa (seventh-eighth century AD) started to deteriorate due lack of protection and surface erosion. The most important issue in the planning of conservation work was to understand such mechanisms and to decrease the effect of salt weathering on structural damage. The purpose of this paper is to discuss these issues. Design/methodology/approach: – Evaporation distribution and salts types were studied on selected walls. In addition, three-dimensional recording of the walls and the stupa was undertaken with digital photogrammetric methods. Findings: – It was clearly found that the intensity of salt weathering in the site is high and some salts such as halite (sodium chloride) are thought to originate from groundwater. On the basis of the results obtained, thick shelter coating with mud brick and mud render was designed and constructed as protective measure for the earthen walls. Practical implications: – Those walls that were most affected by salts weathering and erosion at the base (coving) became structurally less sound and eventually collapsed if not conserved. Originality/value: – The work is the first attempt in the design of a methodology for the selection of earthen repair materials and methods.